PENELITIAN ASPEK LINGKUNGAN FISIK PERAIRAN SEKITAR PELABUHAN SABANG - Edyanto, CB Herman (Jurnal Sains dan Teknologi Indonesia, 2008)
Ports with all ships movement might be one of the busiest center of activities in the coastal areas. It could be understood since ports become the main gates where passengers and goods are collected and distributed from and to entire of state. The affect from these activities may effect to its degradation of waters quality around port because of oil spill, dismissal of chemicals, liquid and solid waste around it. Sabang port lay in an international fairway trajectory which have crisis to oil spill and other discard materials to the territorial waters Understanding the quality of territorial waters will help to overcome the problems which may be faced at a period to come.